Adipose tissue lipolytic inhibition enhances the glucoregulatory properties of exercise in type 2 diabetes patients. Issue 9 (21st October 2018) - Hansen, Dominique; Verboven, Kenneth; van Dijk, Jan-Willem; Zorenc, Antoine; Minten, Lennert; Smeets, Kevin; Verdijk, Lex B.; van Loon, Luc J. C.
ABSTRACT: Aims: Exercise combined with adipose tissue lipolytic inhibition augments intramuscular lipid and glycogen use in type 2 diabetes patients. The present study investigates the impact of adipose tissue lipolytic inhibition during exercise on subsequent postprandial glycemic control in type 2 diabetes patients. Methods: Fourteen male type 2 diabetes patients (age 65 ± 2 years, HbA1c 6.7 ± 0.1% (50 ± 2 mmol/mol)) participated in a double-blind placebo-controlled randomized cross-over study in which subjects performed endurance-type exercise after being administered 250 mg of a nicotinic acid analogue (acipimox; ACP) or a placebo (PLA). A control experiment was included in which no exercise was performed (CON). Results: Sixty minutes of endurance-type exercise (at 45% W peak) did not significantly lower circulating plasma glucose and insulin excursions in PLA when compared with CON ( P = .300). Acipimox administration strongly reduced circulating plasma FFA concentrations during exercise ( P < .001). Circulating plasma glucose and insulin excursions were substantially lower during 7.5 h of recovery from exercise ( i.e. postprandial) in ACP when compared with either CON ( P = .041 and P = .002, respectively) or PLA ( P = .009 and P = .001, respectively). Conclusions: Collectively, exercise with adipose tissue lipolytic inhibition reduces postprandial blood glucose and insulin excursions and, as such, further improves glycemic control in male type 2 diabetes patients.